The Qur'an and Its Implications for Modern Man: Ecological-Based Environmental Conservation Integral Perspective - Andini, Riddo; Arifin, Mohamad Zaenal; Amin, Muhammad; Hikam, Ahmad Bahrul (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This paper with philosophical studies intends to reveal the ideas and concepts contained in the concept of ecology-based environmental conservation integral to the Qur'anic perspective. Environmental conservation based on an integral ecological approach is a new model capable of integrating multiple perspectives into a complex post-disciplinary approach. Within its framework, every issue related to environmental conservation must first be consulted with four irreducible quadrants, namely objective (behavioral field), subjective (experience field), intersubjective (cultural field), and inter-objective (system field). To be able to solve the complexity of the problem comprehensively. This framework in an integrative form includes a psycho-cultural-socio-normative dimension, which demands a multidisciplinary study. The method used in this study is the maudÅ«'i (thematic) interpretation method formulated by RashwÄnÄ«, using integrative-interconnective shortages to understand the complexity of life faced by humans. The Qur'anic perspective on ecological-based environmental conservation is integral to four things: first, responsible behavior for the sustainability of nature (behavioral terrain). Second, ecological awareness (field of experience). Third, the application of religious values in environmental conservation (cultural terrain), including ethics towards animals, and plants. Fourth, obey the rules of the creator (terrain system), by paying attention to threats to perpetrators of environmental destruction and providing appropriate laws for perpetrators of environmental violations.